2019
DOI: 10.15446/dyna.v86n208.72056
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid model to design a distribution network in contract farming

Abstract: This paper suggests a hybrid model to solve a distribution problem incorporating the impact of uncertainty in the solution. The model combines the deterministic approach and the simulation including stochastic variables such as harvest yield, loss risk and penalties/benefits to design a distribution network with the minimal cost. Through a case study that includes farmers, hubs and malt producers in the supplying chain of barley in Mexico, nine possible scenarios were analyzed to plan and distribute the harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…• Los informes empleados debían ser artículos científicos y mejoras de organizaciones de investigación • Las referencias utilizadas debían abordar el tema de las redes de distribución en organizaciones y distribución con transbordo modelados matemáticos de simulación con la finalidad de diagnosticar cuellos de botellas e incrementar la eficiencia de las redes de distribución. Adicionalmente, Granillo- Macías et al (2019) y Vivar-Astudillo et al (2020 realizaron estudios de modelos híbridos enfocados en mejorar los eslabones de las redes de distribución, con el objetivo de optimizar costos y procesos de producción y fortalecer la cadena de distribución. Las características de estos informes se indican en la Tabla 1, que describe el alcance del tema de estudio.…”
Section: Criterios De Inclusión Y Exclusiónunclassified
See 1 more Smart Citation
“…• Los informes empleados debían ser artículos científicos y mejoras de organizaciones de investigación • Las referencias utilizadas debían abordar el tema de las redes de distribución en organizaciones y distribución con transbordo modelados matemáticos de simulación con la finalidad de diagnosticar cuellos de botellas e incrementar la eficiencia de las redes de distribución. Adicionalmente, Granillo- Macías et al (2019) y Vivar-Astudillo et al (2020 realizaron estudios de modelos híbridos enfocados en mejorar los eslabones de las redes de distribución, con el objetivo de optimizar costos y procesos de producción y fortalecer la cadena de distribución. Las características de estos informes se indican en la Tabla 1, que describe el alcance del tema de estudio.…”
Section: Criterios De Inclusión Y Exclusiónunclassified
“…Granillo- Macías et al (2019) determinaron que la satisfacción del cliente debe estar presente en toda actividad comercial, pues las redes de distribución se encargan de fortalecer la cadena de suministros de las empresas por medio de sistenas o modelos que contribuyen al traslado de los productos e insumos desde las fabricas productoras a diferentes destinos finales. Motevalli-Taher et al (2020) dedujeron que el modelo de redes de distribución se compone de varias conexiones entre las fábricas y los centros de acopio, a partir de las cuales se trasladan los productos e insumos desde las plantas hacia los almacenes y distintos puntos de venta, como se muestra en la Figura 2.…”
Section: Redes De Distribuciónunclassified
“…A real-life case study demonstrated the approach as effective. An hybrid deterministic/non-deterministic model was proposed by Granillo et al [15] for minimizing the building cost of a distribution network farm. Results reported for the supply chain of barley in Mexico showed that the model computed accurate solutions.…”
Section: Related Workmentioning
confidence: 99%
“…The set of constraints in Equation (15) indicates that the maximum production capacity of line l must be greater than the quantity produced in that line for every week. Two terms are subtracted from the productivity of the production line l: the stop times needed and the cleanings saved, according to a correct sequencing of the products to be produced.…”
mentioning
confidence: 99%
“…Resellers defend higher distribution costs incurred by arguing that intermediaries perform those activities that would otherwise have to be done by manufacturers or customers (Granillo-Macias, Gonzalez-Hernandez, Martinez-Flores, Caballero-Morales, & Olivares-Benitez, 2019). Higher markup prices result also because of the demands of customers.…”
Section: High Distribution Costsmentioning
confidence: 99%